PERCEPTIONS OF NYAOPE USERS REGARDING THERAPEUTIC SERVICES AT PRIVATE IN-PATIENT TREATMENT CENTRES IN GAUTENG - Zwane, Noxolo Chairmaine Minenhle; Geyer, Stephan (Social Work, 2023)
National data indicate that young adults are increasingly vulnerable to the harmful use of nyaope –an illicit drug. Consequently, there is a need for appropriate treatment services. This study aimedto explore and describe the experiences of nyaope users regarding therapeutic services at privatein-patient treatment centres in Gauteng, South Africa. A qualitative study operationalised througha case study design, specifically an instrumental case study, involved 11 cases/participants whowere recruited through a three-phase non-probability sampling process at treatment centres in twoGauteng metropoles. Following a method of reflexive thematic analysis, four themes withassociated sub-themes, are reported. Recommendations focus on tailored service delivery attreatment centres and addressing limitations in policies. Keywords: Nyaope, treatment centre, in-patient treatment, therapeutic services, case study design, substance use disorder, Gauteng province